Parallel detection of lactobacillus and bacterial vaginosis-associated bacterial DNA in the chorioamnion and vagina of pregnant women at term. (18th August 2019) - Lannon, Sophia M. R.; Adams Waldorf, Kristina M.; Fiedler, Tina; Kapur, Raj P.; Agnew, Kathy; Rajagopal, Lakshmi; Gravett, Michael G.; Fredricks, David N.
Abstract: Background: The majority of early preterm births are associated with intrauterine infections, which are thought to occur when microbes traffic into the uterus from the lower genital tract and seed the placenta. Bacterial vaginosis (BV) is associated with heterogeneous bacterial communities in the vagina and is linked to preterm birth. The extent to which trafficking into the uterus of normal and BV-associated vaginal bacteria occurs is unknown. The study objective was to characterize in parallel the distribution and quantities of bacteria in the vagina, uterus, and placental compartments. Methods: Pregnant women at term (≥37 weeks) presenting for delivery were recruited prospectively. Swabs were collected in parallel from the vagina, chorioamnion. Choriodecidual swabs were collected if a cesarean section was performed. Samples were analyzed by culture, broad-range 16S rRNA gene PCR, and bacterial species-specific quantitative PCR (qPCR) for DNA from Lactobacillus and a panel of BV-associated bacteria. Results were correlated with placental histopathology. Results: Of the 23 women enrolled, 15 were delivered by cesarean section ( N  = 10 without labor; N  = 5 in labor) and eight were delivered vaginally. BV was diagnosed in two women not in labor. Placental histopathology identified chorioamnionitis or funisitis in six cases [1/10 (10%) not in labor; 5/13 (38%) in labor]. Among non-laboring women, broad-range 16S qPCR detected bacteria in the chorioamnion and the choriodecidua (4/10; 40%). Among laboring women, Lactobacillus species were frequently detected in the chorioamnion by qPCR (4/13; 31%). In one case, mild chorioamnionitis was associated with qPCR detection of similar microbes in the chorioamnion and vagina (e.g. Leptotrichia/Sneathia, Megasphaera ), along a quantitative gradient. Conclusions: Microbial trafficking of lactobacilli and fastidious bacteria into the chorioamniotic membranes and choriodecidua occurs at term in normal pregnancies. In one case, we demonstrated a quantitative gradient between multiple bacterial species in the lower genital tract and placenta. Not all bacterial colonization is associated with placental inflammation and clinical sequelae. Further studies of the role of placental colonization with Lactobacillus in normal pregnancy and fastidious bacteria in chorioamnionitis may improve prevention and treatment approaches for preterm labor.